Degradation of glutathione S-conjugates in physcomitrella patens is initiated by cleavage of glycine - Bleuel, Corinna; Wesenberg, Dirk; Meyer, Andreas (Plant & cell physiology, 2011)
Glutathione-dependent detoxification is a key pathway that allows plants to efficiently remove toxic compounds like heavy metals or electrophilic xenobiotics. Under persistent exposure to toxins plants need to respond to continuous demand with efficient synthesis of glutathione (GSH) and ideally fast and efficient removal of potentially toxic glutathione S-conjugates. With the aim of studying the respective degradation pathway in Physcomitrella patens we initially characterized fluorescence labeling of protonema cultures with GSH-specific xenobiotic monochlorobimane (MCB). Incubation of protonema with 200 μM MCB for 24 h resulted in a steady increase of total bimane label, which was not confined to glutathione S-bimane (GS-B), but predominantly present in γ-glutamylcysteine S-bimane (γ-EC-B) and cysteine S-bimane (Cys-B). Pulse-chase experiments identified γ-EC-B and Cys-B as degradation products of GS-B, suggesting initial cleavage of the C-terminal glycine, followed by cleavage of the γ-glutamyl bond. The amount of GS-B formed, increased linearly at 90 nmol GSH g fw−1 h−1 for 24 h and after ∼1.5 h already surpassed the amount of GSH present in control protonema. This demand-driven biosynthesis of GSH depends on sufficient supply of sulfate in the incubation medium.